Penerapan Sistem Informasi Akuntansi dan Pengendalian Internal dalam Mengurangi Salah Saji Laporan Keuangan - Eko Setyanto; Siti Widiana Nurhanifah (Pusat Riset dan Inovasi Nasional, 2024)
The issuance of an opinion on financial statements must be based on the belief that the financial reporting is fairly presented, meaning it is free from material misstatement. At Daarut Tauhiid Foundation, a phenomenon occurred where the financial statements for the years 2018-2020 received a qualified opinion (WDP) due to differences in the beginning and ending net asset balances caused by errors in Excel formulas. Primary data were collected from 54 respondents, including employees involved in the preparation of financial statements, those who have access to the accounting information system, and those engaged in internal control activities. Data processing revealed that the significance of the accounting information system variable was 0.04, the internal control variable was 0.002, and both variables together yielded a result of 0.000, indicating that the accounting information system and internal control simultaneously reduce financial statement misstatements. Ultimately, this study shows that internal control simultaneously reduces financial statement misstatements by 53.4%.